Optimization of Encapsulation of Moringa Oleifera Antioxidant Activity with Ionic Gelation Method Using Sodium Alginate and CaCl2 - Pinto, Floriana A.; Kusumawati, Nita (GoAcademica Research & Publishing, 2024)
The diversity of medicinal plant benefits in Timor Leste. One of them is the Moringa plant which has not been utilized properly such as roots, bark and leaves. Unhealthy living habits can trigger poor human health. Namely malnutrition and exposure to free radicals cause cell damage in the body and ultimately have a major impact on health. Antioxidants as the right effort to be able to ward off and capture free radicals and replace damaged body cells, help in the regeneration of new cells. Antioxidants can be obtained from leaves, bark and roots of Moringa which are rich in high nutrition, encapsulated with Sodium Alginate and CaCl2. The purpose of the study was to determine the physical and chemical characteristics of Moringa leaf, bark and root extracts. Benefits for innovating functional Moringa food products with the highest antioxidant content, namely Moringa leaves. Using the ionic gelation method with nano synthesis testing with variations of Sodium Alginate and CaCl2 with variations in the ratio between (3: 1, 4: 1, and 5: 1). Testing of physical and chemical characteristics of superior results at a ratio of 5: 1. The results of the antioxidant test showed that the best Moringa leaves had an IC50 value of <50 ppm, its effectiveness in inhibiting free radicals was higher than extracts from other parts of Moringa. After encapsulation, the leaf extract yield was 29.81262851 ppm, the bark 40.69652802 ppm, and the roots 43.56171361 ppm